Packaging and storage studies on coconut cookies - Ramirez, Rachel Patricia Bautista; Dumelod, Benelyn Domingo (1995.)
Proximate analysis showed that coconut cookies are high in fiber and fat but low in moisture. Based on suitability to the product, cast polypropylene/vacuum metallized oriented polypropylene (CPP/VMOPP) and polyethylene terephthalate/aluminum/polyethylene (PET/Al/PE) were chosen out of six packaging films for use in the storage studies. Moisture sorption values of coconut cookies were determined using proximity equilibrium cell (PEC) method. Critical moisture content (CMC) was determined by sensory, microbial and physio-chemical tests on products stored at 38°C and 100% RH. From the results, half-value period at experimental and actual conditions were computed and shelf life of the product in the two packaging films estimated. The sorption isotherm of coconut cookies showed that the product is stable at aw values of 0.11 to 0.75. At relative humidities greater than 75%, the product becomes hygroscopic and susceptible to rancidity and microbial activity. The CMC of the product was at 9.40% at which acceptability declined due to changes in the textural properties. The estimated shelf life of coconut cookies at 28°C and 81% RH were 189 days packed in CPP/VMOPP and 1,515 days in PET/Al/PE.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Cookies -- Packaging; Snack foods -- Packaging